Neoclassical factors - Chen, Long 1969-; Zhang, Lu 1972- (National Bureau of Economic Research, 2007)
The cross section of returns can largely be summarized by the market factor and mimicking portfolios based on investment-to-assets and earnings-to-assets motivated from neoclassical reasoning. The neoclassical three-factor model can capture average return variations related to momentum and financial distress anomalous to traditional factor models. The model also captures the relations of average returns with earnings-to-price, cash flow-to-price, book-to-market, dividend-to-price, long-term past sales growth, long-term prior returns, and market leverage.
Literaturverz. S. 33 - 36